Unexpected microbial metabolic responses to elevated temperatures and nitrogen addition in subarctic soils under different land-use - Schroeder, Julia; Peplau, Tino; Gregorich, Edward; Tebbe, Christoph C.; Poeplau, Christopher (Zenodo, 2022)
This repository contains all necessary raw data as well as the R code used to conduct statistical analysis and create figures of the publication Unexpected microbial metabolic responses to elevated temperatures and nitrogen addition in subarctic soils under different land-use Julia Schroeder1, Tino Peplau1, Edward Gregorich2, Christoph C. Tebbe3, Christopher Poeplau1 1 Thünen Institute of Climate-Smart Agriculture, Bundesallee 68, 38116 Braunschweig, Germany 2 Research and Development Centre, Central Experimental Farm, Agriculture and Agri-Food Canada, Ottawa, Canada 3 Thünen Institute of Biodiversity, Bundesallee 65, 38116 Braunschweig, Germany DOI: https://doi.org/10.1007/s10533-022-00943-7 This study investigated how subarctic soils under different land use will respond to warming and increasing N availability to allow for better predictions of C cycling under global change. The short-term temperature sensitivity as well as N-input effects on microbial CUE, respiration, growth and turnover were assessed in a one-day incubation experiment according to the 18O-CUE approach. The warming and N response of SOM decomposition were assessed in a 50-days incubation experiment via measurement of cumulative respiration. Both experiments were conducted with the following three treatments: incubation at 10 °C, incubation at 20 °C, and incubation at 20 °C plus N-fertiliser addition at an amendment rate of 100 kg N ha-1. The response to warming or N addition were expressed as response ratios RRT = 20°C/10°C and RRN = 20°C+N/20°C for warming and N response, respectively. The R code was developed under R v3.6.3 and adapted to work under version R v.4.1.2. The repository includes the following files: general_soil_parameters_per_sample.csv - general soil data for each field sample (n=27) general_soil_parameters_per_plot.csv - general soil data assessed on pooled replicated field samples (n=9) respiration_over_50d_incubation.csv - respiration rate and cumulative respiration for each time-point and laboratory sample over the ...